2018
DOI: 10.18089/tms.2018.14107
|View full text |Cite
|
Sign up to set email alerts
|

Business model innovation: towards a conceptual framework

Abstract: Business model innovation (BMI) is core for entrepreneurship in industrial or service sectors, including tourism. Our submission focuses on the development of the field of BMI. We perform systematic literature review based on 316 valid papers indexed on ISI Current Contents, published between 2000 and 2015.Bibliometric results indicate a significant increase in the number of papers, journals and authors, and lack of specialized journals/authors publishing regularly in the BMI field. Thematic analysis reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
1
0
3
Order By: Relevance
“…Innovating technologically is an indispensable requisite for exploring new opportunities [87], entering into competition superbly [88] and becoming a competent contender in the global market [89]. Previous literature has confirmed that firms engaged in TI generate growth, create value, and outperform others [90] and that TI is imperative for driving a firm's competitive advantage [91] and national development [92].…”
Section: The Mediating Role Of Technological Innovation In the Relatimentioning
confidence: 99%
“…Innovating technologically is an indispensable requisite for exploring new opportunities [87], entering into competition superbly [88] and becoming a competent contender in the global market [89]. Previous literature has confirmed that firms engaged in TI generate growth, create value, and outperform others [90] and that TI is imperative for driving a firm's competitive advantage [91] and national development [92].…”
Section: The Mediating Role Of Technological Innovation In the Relatimentioning
confidence: 99%
“…Criar modelos de negócios inovadores é essencial para o desenvolvimento do empreendedorismo no setor de turismo (Amaral;Soares;Proença, 2018), criando valor e agregando receitas para os empreendimentos turísticos. A criação de novos modelos de negócios é uma forma de evitar o declínio organizacional diante de turbulência e incerteza.…”
Section: Modelos De Negóciosunclassified
“…Para Ammirato et al (2021), em geral, modelo de negócio é uma ferramenta conceitual que permite a identificação dos principais componentes de um negócio (ou seja, receitas, custos, fornecedores, canais, etc.). O modelo de negócio pode ser definido como um conjunto de elementos que permitem configurar o negócio criando valor para a empresa (Amaral;Soares;Proença, 2018), onde a essência do modelo de negócio é definir como a empresa entrega "valor aos clientes, atrai clientes para pagar por esse valor e converte esses pagamentos em lucro" (Teece, 2010, p.172). Em resumo, é como a empresa gera lucros.…”
Section: Modelos De Negóciosunclassified
“…Son 15 yılda iş modeli inovasyonu, yönetim alanındaki araştırmalarda ve uygulayıcılar arasında yoğun ilgi gören bir inceleme konusu haline gelmiştir. İş modeli inovasyonuyla ilgili gelişmekte olan yazın, önemli bir olguya işaret etmekle birlikte teorik temelden yoksun olduğu ve konuyla ilgili deneysel araştırmaların da yeterli birikime sahip olmadığı belirtilmektedir (Foss & Saebi, 2017;Saur-Amaral, Soares, & Proença, 2018). Ayrıca, yapılan çalışmalar benimsenen yöntem açısından değerlendirildiğinde, önemli miktarda çalışmada keşifsel araştırma tasarımı çerçevesinde örnek olay çalışması ya da diğer nitel araştırma yöntemlerinden birinin kullanıldığı; iş modeli inovasyonuyla ilgili kavramsal modellerin geliştirilmesi ve deneysel olarak test edilmesi ya da mevcut test edilmiş modellerin nicel ya da karma araştırma yöntemi benimsenerek yeni veri setiyle geçerli kılınması gibi çalışmalara gereksinim olduğu belirtilmektedir (Saur-Amaral ve diğerleri, 2018).…”
Section: Innovation Radarunclassified